2011
DOI: 10.1097/aog.0b013e31823835d3
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Delivery in Nulliparous Women and Neonatal Intracranial Injury

Abstract: OBJECTIVE To compare neonatal neurologic complication rates of cesarean deliveries, forceps-assisted vaginal deliveries, and vacuum-assisted vaginal deliveries. METHODS Data on singleton live births at 34 weeks or greater gestation born to nulliparous women from 1995 to 2003 in New York City were linked to hospital discharge data. Any diagnosis of neonatal subdural hemorrhage, intraventricular hemorrhage, seizures, scalp laceration or cephalohematoma, fracture, facial nerve palsy, brachial plexus injury, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
39
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 18 publications
10
39
0
2
Order By: Relevance
“…This is in line with the results of previous studies [10,12,14] . Regarding the distribution of 5-min Apgar values, there were more 5-min Apgar values ≤ 5 in the CS group.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This is in line with the results of previous studies [10,12,14] . Regarding the distribution of 5-min Apgar values, there were more 5-min Apgar values ≤ 5 in the CS group.…”
Section: Discussionsupporting
confidence: 83%
“…Regarding the distribution of 5-min Apgar values, there were more 5-min Apgar values ≤ 5 in the CS group. A previous investigation [14] also presented a higher rate of Apgar scores (<7) in the CS group than deliveries by forceps. Another study [12] demonstrated a higher percentage of 5-min Apgar scores (<7) regardless of the indication for delivery in their CS group in comparison to instrumentalassisted deliveries, but the differences were not significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several retrospective studies comparing neonatal morbidity after CD v. AVD have been published. Werner et al [16] found that forceps deliveries were associated with a significantly reduced risk of adverse neonatal neurological outcome (when regarding seizures and intraventricular and subdural haemorrhage as the morbidities most predictive of future neurodevelopmental deficits). Forceps delivery was also IPA+T rate, /1 000 Ventouse deliveries, % Fig.…”
Section: Fetal Indicationsmentioning
confidence: 99%
“…56, 7 However, when a woman has a need for intervention in the second stage, spontaneous vaginal delivery is not an option she or the provider can choose. The appropriate clinical comparison is cesarean versus operative vaginal delivery.…”
Section: Introductionmentioning
confidence: 99%